2018
DOI: 10.1093/cercor/bhy268
|View full text |Cite
|
Sign up to set email alerts
|

High-Expanding Regions in Primate Cortical Brain Evolution Support Supramodal Cognitive Flexibility

Abstract: Primate cortical evolution has been characterized by massive and disproportionate expansion of a set of specific regions in the neocortex. The associated increase in neocortical neurons comes with a high metabolic cost, thus the functions served by these regions must have conferred significant evolutionary advantage. In the present series of analyses, we show that evolutionary high-expanding cortex – as estimated from patterns of surface growth from several primate species – shares functional connections with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 79 publications
2
15
0
Order By: Relevance
“…Within the DMN those regions with low FHI are the same regions that in humans contain the most information about global brain dynamics. Together these results are consistent with a complex view of cross species differentiation which impacts on cortical modules at both a local and global scale 17,66,68,71,72 .…”
Section: Discussionsupporting
confidence: 87%
“…Within the DMN those regions with low FHI are the same regions that in humans contain the most information about global brain dynamics. Together these results are consistent with a complex view of cross species differentiation which impacts on cortical modules at both a local and global scale 17,66,68,71,72 .…”
Section: Discussionsupporting
confidence: 87%
“…These three measures reflect different fundamental aspects of brain organization in which higher values reflect diminished constraints of sensory and structural input and increased capacity to support a wider array of different tasks such as higher-order cognition (4,28,29). Fig.…”
Section: Relationship Of Lifespan Encoding Clusters With Large-scale mentioning
confidence: 99%
“…Over the last few years, research has demonstrated that the structural foundations of general cognitive abilities are largely constant throughout life (1, 2), being embedded into fundamental aspects of brain organization as captured by evolutionary expansion patterns or connectivity gradients (3,4). However, it is unknown whether the functional foundations supporting specific forms of cognition are equally stable or rather dynamic through life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sneve et al discuss the beneficiary cognitive gains the 'massive and disproportionate expansion' of parts of the neocortex conferred upon ussupporting selective brain growththrough cross comparison of histological and neuroimaging data from several primate species, including sapiens. 5 High-expanding cortical regionsnotably the lateral temporal, parietal and prefrontal corticesare characterised by significant internetwork connectivity and flexible recruitment across a range of different cognitive tasks. The authors propose that it is the sheer flexibility of these expanding cortical 'hotspots' to connect with and integrate multiple different brain regions depending on cognitive and emotional needssupramodal cognitionthat sustained and supported their evolutionary selection over the ages.…”
mentioning
confidence: 99%